Eigenvalue inclusion sets for linear response eigenvalue problems - He Jun; Liu Yanmin; Lv Wei (Demonstratio Mathematica, 2022)
In this article, some inclusion sets for eigenvalues of a matrix in the linear response eigenvalue problem (LREP) are established. It is proved that the inclusion sets are tighter than the Geršgorin-type sets. A numerical experiment shows the effectiveness of our new results.